2020
DOI: 10.3390/ijms21217987
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Photosynthetic Activity of Selected Spelt Varieties (Triticum aestivum ssp. spelta L.) Cultivated under Drought Conditions with Different Endophytic Core Microbiomes

Abstract: The role of the microbiome in the root zone is critically important for plants. However, the mechanism by which plants can adapt to environmental constraints, especially water deficit, has not been fully investigated to date, while the endophytic core microbiome of the roots of spelt (Triticum aestivum ssp. spelta L.) grown under drought conditions has received little attention. In this study, we hypothesize that differences in the endophytic core of spelt and common wheat root microbiomes can explain the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…spelta L.) roots under drought conditions is poorly understood. Ratajczak et al [13] found that inoculating the tolerant 'Badenstern' variety with the mycorrhizal fungus R. irregularis contributed to improved growth performance. The inoculation of less tolerant varieties (such as "Zollernspelz") also produces positive effects on the roots under stress.…”
Section: Drought Stressmentioning
confidence: 99%
“…spelta L.) roots under drought conditions is poorly understood. Ratajczak et al [13] found that inoculating the tolerant 'Badenstern' variety with the mycorrhizal fungus R. irregularis contributed to improved growth performance. The inoculation of less tolerant varieties (such as "Zollernspelz") also produces positive effects on the roots under stress.…”
Section: Drought Stressmentioning
confidence: 99%
“…These mechanisms include gas exchange, chlorophyll fluorescence, relative water content, lipid peroxidation index, proline, and anthocyanins accumulation, and facilitate the development of different genetic approaches to improve plant drought resistance and prevention of yield loss in economically important wheat. In contrast to common wheat, only a few studies assessed the spelt wheat's resistance to water shortages [5][6][7][8]. The effect of drought stress on the physiological properties and the course of the photosynthesis process in spelt wheat have not been fully characterized and explained.…”
Section: Introductionmentioning
confidence: 99%
“…A striking example of this are the major changes observed in root‐associated fungal communities in Triticum aestivum plants under drought stress (Salamon et al, 2020 ). Another study from the same group pointed into the same direction, highlighting that drought stress indirectly affected the plant−fungal interactions in roots of T. aestivum (subspecies vulgare and spelta ), while still promoting plant growth and several physiological parameters, including photosynthetic activity, electron transport rate and water use efficiency (Ratajczak et al, 2020 ).…”
Section: Plant−microbe Interactions Are Compromised In Stress Situationsmentioning
confidence: 89%